Facies architecture and depositional evolution of the Middle Eocene mass flow- dominated fan delta complex in the multifeeder areas: Elazığ Marine Basin (Eastern Türkiye) - Alkac, Onur (Tubitak Scientific & Technological Research Council Turkey, 2024)
The mass flow-dominated fan delta complex is developed by the rapid deposition of coarse-grained materials in front of uplifted areas under the influence active tectonism. This is important for providing clues about the first opening stages of marine basins. The study aims to shed light on the fact that mass flow-dominated fan delta complexes play an active role in determining the characterization of tectonism controlling basin opening. In the study area, mass flow-dominated deposits of the Delikta & scedil; Fan Delta Complex (DFDC) represent the first deposits of the southern part of the Middle Eocene Elaz & imath;& gbreve; Marine Basin, whose development is controlled by normal block faults. The basin consists of the alluvial fan succession, the fan delta succession and the turbidite succession overlying both successions. DFDC is composed of fan delta facies assemblages deposited in the form of shallow water coastal prism in front of the multifeeder areas controlled by extensional tectonism. Conglomerates and sandstones predominate in the DFDC successions. The system forming the DFDC is a good example for high-energy, mass flow-dominated, multifeeder fan delta environments with different source areas surrounding the Elaz & imath;& gbreve; Basin from the north and south. Sedimentological studies were carried out from 11 measured stratigraphic sections taken from the DFDC, and three different sequences were defined. These sequences contain the deposits belonging to fan delta plain and fan delta front facies assemblages. The facies architecture of the successions of the DFDC was defined based on measured stratigraphic sections, litho-correlation and field observations, and with the help of the obtained data, the sedimentation evolution of the sequences belonging to it was revealed with three-dimensional basin models. In this way, an approach to the primary geodynamics of the Elazi & gbreve; Basin was obtained.
Keywords: Fan delta complex; facies architecture; marine basin; primary geodynamics; paleogeographic control